Nonenzymatic Glucose Biosensors Based on Silver Nanoparticles Deposited on TiO2 Nanotubes - Zheng Li; Yong Zhang; Jiaye Ye; Meiqing Guo; Jing Chen; Weiyi Chen (Journal of Nanotechnology)
In the present research, a nonenzymatic glucose biosensor was fabricated by depositing Ag nanoparticles (Ag-NPs) using in situ chemical reduction method on TiO2 nanotubes which were synthesized by anodic oxidation process. The structure, morphology, and mechanical behaviors of electrode were examined by scanning electron microscopy and nanoindentation. It was found that Ag-NPs remained both inside and outside of TiO2 nanotubes whose length and diameter were about 1.2 μm and 120 nm. The composition was constructed as an electrode of nonenzymatic biosensor for glucose oxidation. The electrocatalytic properties of the prepared electrodes for glucose oxidation were investigated by cyclic voltammetry (CVs) and differential pulse voltammetry (DPV). Compared with bare TiO2 and Ag-fresh TiO2 nanotube, Ag-TiO2/(500°C) nanotube exhibited the best electrochemical properties from cyclic voltammetry (CVs) results. Differential pulse voltammetry (DPV) results showed that, at +0.03 V, the sensitivity of the electrode to glucose oxidation was 3.69 mA⁎cm-2⁎mM-1 with a linear range from 20 mM to 190 mM and detection limit of 24 μM (signal-to-voice ratio of 3). In addition the nonenzymatic glucose sensors exhibited excellent selectivity, stability, and repeatability.